2019
DOI: 10.1016/j.fertnstert.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of air pollutants on spontaneous pregnancy loss: a case-crossover study

Abstract: Objective: To investigate the relationship between acute exposure to air pollutants and spontaneous pregnancy loss. Design: Case-crossover study from 2007 to 2015. Setting: An academic emergency department in the Wasatch Front area of Utah. Patient(s): A total of 1,398 women who experienced spontaneous pregnancy loss events. Intervention(s): None. Main Outcome Measure(s): Odds of spontaneous pregnancy loss. Result(s): We found that a 10-ppb increase in 7-day average levels of nitrogen dioxide was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 31 publications
3
49
1
2
Order By: Relevance
“…Some studies have investigated the associations between maternal exposure to NO 2 and SAB. Most of those reported studies used xed air monitoring station data to estimate individual NO 2 exposure and reported signi cant positive associations between NO 2 exposure and SAB risk [18,19,23,24]. Our ndings were consistent with the results of those previous studies.…”
Section: Sabsupporting
confidence: 92%
“…Some studies have investigated the associations between maternal exposure to NO 2 and SAB. Most of those reported studies used xed air monitoring station data to estimate individual NO 2 exposure and reported signi cant positive associations between NO 2 exposure and SAB risk [18,19,23,24]. Our ndings were consistent with the results of those previous studies.…”
Section: Sabsupporting
confidence: 92%
“…Often the choice falls on regression models. Both time-series (Bell et al 2004;Zheng et al 2015;Jie et al 2018) and case-crossover designs are widely used (Taj et al 2017;Leiser et al 2018). Although, in addition to these consolidated study designs, for the same purposes, also other methods are being routinely used, e.g., crosssectional studies or case-control studies (Nieuwenhuijsen 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have uncovered a positive association between pollution and spontaneous abortion ( Leiser et al, 2019 ; Zhang et al, 2019 ), so our analyses presented here allow for more specific hypotheses regarding the potential chemicals that might cause preferential abortions of male or female fetuses. Fortunately, most of the putative positive associations identi1ed in our study are experimentally testable, at least with animal models.…”
Section: Discussionmentioning
confidence: 99%
“…, terrorist attacks and earthquakes), radiation, weather parameters, and even seasons of conception (Table 1). While there are multiple studies in which the positive associations between air pollution and spontaneous abortion have been observed ( Leiser et al, 2019 ; Zhang et al, 2019 ), most of those conclusions were drawn based on analyses of relatively small samples (Table 1). In this study, we harnessed the power of two very large datasets: MarketScan’s insurance claim data ( Hansen, 2017 ) in the United States (more than 100 million unique patients and more than three million unique newborns recorded between 2003 to 2011), and Sweden’s birth registry data (∼ 3.2 million newborns from 1983 to 2013) ( Emilsson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%